Indoline-based donor-pi-acceptor visible-light responsive organic dyes for dye-sensitized solar cells: co-sensitization with squaraine dye for panchromatic IPCE response - Singh, Ambarish Kumar; Nithyanandhan, Jayaraj (ACS Applied Energy Materials, 2022)
A series of metal-free indoline-based donor-pi-acceptor (D-pi-A) visible-light active organic dyes, where an indoline unit wrapped with alkyl or alkyl and glycolic (TEG) groups is used as a donor, a mono- or bi-thiophene unit is used as a pi-spacer, and cyanoacrylic acid acts as an acceptor unit, have been designed and synthesized for dye-sensitized solar cell (DSSC) application. These dyes showed three absorption bands in a dichloromethane solution: the first and second transitions are observed in the UV (337-385 nm) and visible (477-514 nm) regions and correspond to pi-pi* and intramolecular charge transfer (ICT) transition, respectively, whereas the third absorption band obtained in the near-IR (629-758 nm) region has been observed for the first time for a D-pi-A type dye architecture. Furthermore, the ICT transition band for AKT dyes showed negative solvatochromism with increasing polarity of solvents. Photovoltaic characterizations for AKT dyes have been systematically studied with a cobalt electrolyte to evaluate the effect of thiophene incorporation and alkyl group substitution by the TEG group on the DSSC device performance. Here, AKT2 showed the highest DSSC efficiency of 3.16% with V-OC of 0.680 V and J(SC) of 6.24 mA/cm(2) without chenodeoxycholic acid (CDCA) in the AKT dye series, whereas DSSC efficiencies for AKT dyes were not affected much upon further addition of CDCA. Furthermore, AKT dyes were co-sensitized with a complementary optical responsive indoline-based SQS4 dye and showed enhanced efficiency. The combination of AKT2/SQS4 dyes with a ratio of 1:1 showed a maximum of 5.20% co-sensitized solar cell efficiency compared to other dye combinations with the cobalt electrolyte.
Keywords: Dye-sensitized solar cells; indoline-based donor-pi-acceptor dye; intramolecular charge transfer; metal-free organic dye; panchromatic-light absorption; Solvatochromism